L21 P42, a 23AA domain of the huntingtin protein: its protective properties and its modes of action. (13th September 2016) - Maschat, Florence; Couly, Simon; Marelli, Cecilia; Vignes, Michel; Paucard, Alexia; Benigno, Lorraine; Maurel, Patrick; Jourdan, Christophe; Bonneaud, Nathalie
Abstract : Background: Protective properties of P42 were studied in different models of Huntington's disease (HD): HeLa cells, but also Drosophila and R6/2 models of HD. Our results identified that P42 prevents different phenotypes induced by the expression of the mutant protein, including aggregation process, defects in axonal trafficking and neurodegeneration. As a result P42 is able to rescue motor deficits but also anxiety and memory defects. We also showed that P42 is able to prevent but also to treat some of the phenotypes/symptoms of HD. Aims and results: The study of the modes of action of P42 identified that P42 acts at different levels: i) it interacts with N17 domain, therefore preventing the first steps of the aggregation process; ii) as a part of the Htt protein, we analysed its role in vesicular trafficking along the axons, and found that P42 is one of the microtubule binding domain of the Htt protein and it is acting as an enhancer of the vesicular trafficking; iii) we also found that P42 is able to enhance the level of expression of cortical BDNF, defective in the context of the disease; iv) finally we identified a role of P42 in neuronal plasticity and activity. Conclusions: These data showed that P42 allows different entry points in the disease, explaining its impact in both pre- and post-symptomatic windows. It is able to target the disease at different levels, not only by lowering the negative effect of the mutant polyQ-Htt, but also by enhancing the physiological functions of the normal Htt protein.